APLIKASI INFORMASI LOKASI DAN RUTE PASAR MODERN DAN TRADISIONAL DI KOTA SEMARANG BERBASIS ANDROID (Information Technology and Telematics, 2015)
Abstract- Market in the city of Semarang is one container of economic activity in a region. In general, the market is always associated with the transaction between buyers and sellers meet directly and there is usually a price bargaining process. Traditional markets into a shopping center staples are much in demand especially among medium and is often found in several locations near the house, while the modern market is a market that has good management and managed by the system. System development method used in this study is a prototype consisting of analysis, design, create prototypes, evaluation and improvement, results. System design using OOD which consists of the use case diagrams and activity diagrams. Making the program by using the Android programming. The end result of this research is the application of information and the location of the modern and the traditional market in the city of Semarang-based android can be used to display information and the location of the modern and the traditional market in the city of Semarang, which consists of a gallery and the location or route of the selected market if the application can find the position of the current user Keywords – Market, OOD, Android, Prototype